Evidence for genes associated with the ability of Mycobacterium avium subsp. hominissuis to escape apoptotic macrophages - Bermudez, Luiz; Danelishvili, Lia; Babrak, Lmar; Phan, Tuam (Frontiers in Cellular and Infection Microbiology, 2015)
Mycobacterium avium subsp. hominissuis (MAH) is an environmental bacteria that infects immunocompromised humans. MAH cases are increasing in incidence, making it crucial to gain knowledge of the pathogenic mechanisms associated with the bacterium. MAH infects macrophages and after several days the infection triggers the phagocyte apoptosis. Many of the intracellular MAH escape the cell undergoing apoptosis leading to infection of neighboring macrophages. We screened a transposon bank of MAH mutants in U937 mononuclear phagocytes for the inability to escape macrophages undergoing apoptosis. Mutations in genes; MAV_2235, MAV_2120, MAV_2410 and MAV_4563 resulted in the inability of the bacteria to exit macrophages upon apoptosis. Complementation of the mutations corrected the phenotype either completely or partially. Testing for the ability of the mutants to survive in macrophages compared to the wild type bacterium revealed that the mutant clones were not attenuated up to 4 days of infection. Testing in vivo, however, demonstrated that all the MAH clones were attenuated compared with the wildtype MAC 104 in tissues of mice. Although the mechanism associated with the bacterial inability to leave apoptotic macrophages is unknown, the identification of macrophage cytoplasm targets for the MAH proteins suggest that they interfere either with protein degradation machinery or post-translation mechanisms. The identification of tatC as a MAH protein involved in the ability of MAH to leave macrophages, suggests that secreted effector(s) are involved in the process. The study reveals a pathway of escape from macrophages, not shared with Mycobacterium tuberculosis.